Russian architecture in the commercial port of Changchun - Tceluiko, Dmitry (project baikal, 2025)
The work comprehensively depicts the Russian development of the commercial port area in Changchun. The article studies the reasons for the formation and development of the district and shows its economic potential, which led to the creation of several steam mills. The article describes the presence of trade missions of Russian companies. A large block of text is devoted to the architecture of the former consulate of the Russian Empire and its significance in the modern development. In conclusion, the author provides a general summary on Russian architecture and its place and influence within the framework of the new ‘commercial port’ district and in the context of modern development in the city of Changchun.
Keywords: Changchun; commercial port; consulate; Russian architecture; architectural heritage; SMR; Manchuria